The 8200 calBP "climate event" and the process of neolithisation in south-eastern Europe - Budja, Mihael (Documenta Praehistorica, 2007)
Climate anomalies between 8247-8086 calBP are discussed in relation to the process of transition farming and to demographic dynamics and population trajectories in south-eastern Europe.
Keywords: neolitik; klimatske spremembe; prebivalstvo; demografske spremembe; human migration; migracije; jugovzhodna Evropa